A determinant‐free method to simulate the parameters of large Gaussian fields. Issue 1 (15th August 2017) - Ellam, Louis; Strathmann, Heiko; Girolami, Mark; Murray, Iain
Abstract : We propose a determinant‐free approach for simulation‐based Bayesian inference in high‐dimensional Gaussian models. We introduce auxiliary variables with covariance equal to the inverse covariance of the model. The joint probability of the auxiliary model can be computed without evaluating determinants, which are often hard to compute in high dimensions. We develop a Markov chain Monte Carlo sampling scheme for the auxiliary model that requires no more than the application of inverse‐matrix‐square‐roots and the solution of linear systems. These operations can be performed at large scales with rational approximations. We provide an empirical study on both synthetic and real‐world data for sparse Gaussian processes and for large‐scale Gaussian Markov random fields. Copyright © 2017 John Wiley & Sons, Ltd.